Tradisi Hopong Ngae: Solidaritas Sosial dan Implikasi Teologi Kontekstual di Jemaat GMIT Sonaf Neka-Huilelot - Nulik, Eritrika Adriana; Ruku, Welfrid Fini (Fidei: Jurnal Teologi Sistematika dan Praktika, 2025)
The Hopong Ngae tradition in the GMIT Sonaf Neka-Huilelot congregation on Semau Island plays a crucial role in strengthening the congregation's social and spiritual solidarity. This study examines the meaning of solidarity, the continuity of tradition amidst modernization, and its relationship to the actualization of Christian faith in local culture. The method used is a descriptive qualitative approach with in-depth interviews and congregation surveys, combined with simple quantitative analysis. The results show that Hopong Ngae strengthens relationships among congregation members, serves as an expression of gratitude for God's blessings before the harvest, and is also a means of cultural preservation. From Durkheim's perspective, this tradition represents mechanical solidarity that binds congregation members through shared values and goals. Theological reflection confirms that Hopong Ngae can be a medium for contextualizing Christian faith in the congregation's agrarian life. However, challenges arise from the lack of involvement of the younger generation and the influence of globalization. One solution is to empower youth through the use of digital technology to produce creative content on social media. This effort is expected to encourage the participation of the younger generation in maintaining the sustainability of the tradition in the future.AbstrakTradisi Hopong Ngae di Jemaat GMIT Sonaf Neka-Huilelot, Pulau Semau, berperan penting dalam memperkuat solidaritas sosial dan spiritual jemaat. Penelitian ini menelaah makna solidaritas, keberlangsungan tradisi di tengah modernisasi, serta kaitannya dengan aktualisasi iman Kristen dalam budaya lokal. Metode yang digunakan ialah pendekatan kualitatif deskriptif dengan wawancara mendalam dan survei jemaat, dipadukan dengan analisis kuantitatif sederhana. Hasil penelitian menunjukkan bahwa Hopong Ngae mempererat relasi warga jemaat, menjadi ungkapan syukur atas berkat Tuhan menjelang panen, sekaligus sarana pelestarian budaya. Dalam perspektif Durkheim, tradisi ini merepresentasikan solidaritas mekanik yang mengikat anggota jemaat melalui nilai dan tujuan bersama. Refleksi teologis menegaskan bahwa Hopong Ngae dapat menjadi medium kontekstualisasi iman Kristen dalam kehidupan agraris jemaat. Namun, tantangan muncul berupa minimnya keterlibatan generasi muda dan pengaruh globalisasi. Salah satu solusi ialah memberdayakan kaum muda melalui pemanfaatan teknologi digital untuk menghasilkan konten kreatif di media sosial. Upaya ini diharapkan mendorong partisipasi generasi muda dalam menjaga keberlanjutan tradisi di masa depan.